A prospective study comparing water only with positive oral contrast in patients undergoing abdominal CT scan - Pascale A. M. de Wit; Jeroen A. W. Tielbeek; Pascal R. van Diepen; Ikrame Oulad Abdennabi; Ludo F. M. Beenen; Shandra Bipat (Scientific Reports, 2020)
Abstract Consecutive adults scheduled to undergo abdominal CT with oral contrast were asked to choose between 1000 ml water only or positive oral contrast (50 ml Télébrix-Gastro diluted in 950 ml water). Two abdominal radiologists independently reviewed each scan for image quality of the abdomen, the diagnostic confidence per system (gastrointestinalsystem/organs/peritoneum/retroperitoneum/lymph nodes) and overall diagnostic confidence to address the clinical question (not able/partial able/fully able). Radiation exposure was extracted from dose reports. Differences between both groups were evaluated by Student’s t-test, Mann-Whitney-U-test or chi-square-test. Of the 320participants, 233chose water only. All baseline characteristics, image quality of the abdomen and the diagnostic confidence of the organs were comparable between groups and both observers. Diagnostic confidence in the water only group was more commonly scored as less than good by observer1. The results were as follows: the gastrointestinal system(18/233vs1/87; p = 0.031), peritoneum (21/233vs1/87; p = 0.012), retroperitoneum (11/233vs0/87; p = 0.040) and lymph nodes (11/233vs0/87; p = 0.040). These structures were scored as comparable between both groups by observer2. The diagnostic confidence to address the clinical question could be partially addressed in 6/233 vs 0/87 patients (p = 0.259). The water only group showed a tendency towards less radiation exposure. In summary, most scan ratings were comparable between positive contrast and water only, but slightly favored positive oral contrast for one reader for some abdominal structures. Therefore, water only can replace positive oral contrast in the majority of the outpatients scheduled to undergo an abdominal CT.